Water services and climate change: Winning innovations delivering greater resilience - Geneviève Leboucher; Sandrine Oberti (Field Actions Science Reports)
Climate change places our water resources under enormous pressure. Depending on the particular region, it leads to increasing shortages, severe droughts and ever-growing pressure on essential infrastructure. Water services have to evolve if they are to deal with these urgent challenges. Innovation plays a crucial role in this transformation: advanced leak detection techniques, proactive management of corrosion, and reuse of treated wastewater are all key solutions for optimizing how this precious resource is managed and guaranteeing a reliable supply.And the challenges don’t end there. To stave off water stress and preserve this vital resource, there is an urgent need to adopt alternative strategies such as groundwater recharging, forward planning to anticipate vulnerabilities in drinking water production systems triggered by climate change, and rolling out frugal solutions that use less water. It is equally vital that sewer systems are reinforced so they can better deal with heavy rainfall and pollution.Read on to discover how these solutions are transforming water management and tackling climate challenges while also working to protect public health.